A Complexity-Aware Video Adaptation Mechanism for Live Streaming Systems. (3rd June 2007) - Lu Lu, Meng-Ting Meng-Ting; Yao Yao, Jason J. Jason J.; Chen Chen, Homer H. Homer H.
Abstract : The paradigm shift of network design from performance-centric to constraint-centric has called for new signal processing techniques to deal with various aspects of resource-constrained communication and networking. In this paper, we consider the computational constraints of a multimedia communication system and propose a video adaptation mechanism for live video streaming of multiple channels. The video adaptation mechanism includes three salient features. First, it adjusts the computational resource of the streaming server block by block to provide a fine control of the encoding complexity. Second, as far as we know, it is the first mechanism to allocate the computational resource to multiple channels. Third, it utilizes a complexity-distortion model to determine the optimal coding parameter values to achieve global optimization. These techniques constitute the basic building blocks for a successful application of wireless and Internet video to digital home, surveillance, IPTV, and online games.